Os Limites ao Reconhecimento de Adolescentes e seus Contextos Jurídicos Culturais: uma Ilustração com o Caso Brasileiro = The Limitations on the Recognition of Adolescents and their Legal Cultural Contexts : an Ilustration of the Brazilian Case - Costa, Ana Paula Motta (Oñati Socio-Legal Series, 2016)
Recognizing contextualized subject is giving visibility to the status of person, the possibility of manifestation of identity. It materializes through indifference to the social differences that prevent the equal level identification. Nowadays, the struggle for justice and recognition is not an individual problem, it is important to the society as a whole. For adolescents, the limits of recognition can be seen in different dimensions, wherein the step of life with its own cultural features; the particularly difficult economic conditions; cultural legal perspective from the impossibility of intercultural dialogue; and yet, the boundaries of the state, absent in the effectiveness of rights. This reality is revealed in when observing the mortality rates of this public in recent years in Brazil. Young people between 15 and 19 years are the main victims of homicides in the country: 87.6 % of cases (data NEV -USP). These deaths occur mainly where there is an overlap gap and violation of rights. Violence is a complex process, but it is imperative to dialogue and respect the difference, which must be a starting point in relation to where you want to reach: that is to respect the others as equal, without prejudiced ideas.